Effectiveness of CCD ionospheric monitors for air navigation based on GBAS: Investigation and implementation under low geomagnetic latitude conditions - Costa, Renan Rodrigues Toledo; De Oliveira, Paulo Sergio; Klein, Ivandro; Tauil, Giovanni Caramagno; Monico, João Francisco Galera [UNESP]; Dos Reis, Thiago Tietdke; da Costa Silva, Weverton [UNESP] (Elsevier, 2025)
This study investigates the effectiveness of the Code Carrier Divergence (CCD) monitor in dynamic Unmanned Aerial Vehicle (UAV) scenarios, focusing on enhancing GBAS integrity and operational reliability against ionospheric disturbances caused by plasma irregularities. Special attention is given to low-latitude regions such as Brazil, where ionospheric scintillation activity is intense, variable, and difficult to predict, posing a challenge to the reliability of GNSS-based positioning. A series of flight simulations were conducted under varying altitudes and ionospheric conditions to assess the CCD monitor’s ability to detect satellite faults. These faults are typically characterized by divergence between pseudorange and carrier-phase measurements, often caused by sharp ionospheric electron density gradients arising from ionospheric irregularities or localized plasma density enhancements. The CCD technique was applied to monitor these deviations in real-time and support satellite exclusion decisions to preserve navigation performance. The results demonstrate that the CCD monitor is capable of effectively identifying satellites impacted by ionospheric disturbances. In particular, the exclusion of satellites exceeding the CCD threshold during periods of strong ionospheric activity led to notable improvements in positioning accuracy. For example, in one high-activity flight, the standard deviation in the north–south positioning component was reduced from 4.44 m to 0.87 m, and in the east–west component from 1.20 m to 0.87 m. Furthermore, the study explores the relationship between CCD alert thresholds and the formal accuracy of next-generation GNSS observables, including traditional L1 signals and modern signals such as GPS L5. These findings confirm that the CCD-based monitoring approach contributes to improved system integrity and robustness, particularly in environments subject to ionospheric anomalies. Overall, the study highlights the value of integrating CCD monitoring into GBAS architectures to ensure safer and more reliable GNSS navigation in aviation, especially in equatorial regions with high ionospheric variability.